Monetary Policy from an Islamic Perspective: Challenges and Requirements - Salgireeva , Birlant (Dirasat: Shari’a and Law Sciences, 2023)
Objectives: The study aims to introduce monetary policy from an Islamic perspective, clarify the challenges facing Islamic monetary policy and ways to confront them, and define the controls and foundations of Islamic monetary policy. Methods: The study followed the inductive approach, by collecting scientific material from ancient and modern jurisprudence and economics books, and the analytical approach, by analyzing the scientific material and benefiting from it in the subjects of the study. Results: The study concluded that the Islamic monetary policy is the one that guarantees stability in general, the stability of transactions, and continuous economic growth. The Islamic monetary policy faces several challenges, most notably: the interdependence of the global economic system with each other, the domination of the major economic powers, especially the United States of America, over the economies of the world, and the correlation of the currencies of most Arab and Islamic countries with the dollar. One of the proposals to deal with these challenges is that the Arab and Islamic countries reform their monetary and banking system in the light of Islamic teachings, the basis of which is the prohibition of usury, and move away from the capitalist banking system based on the interest rate. Conclusions: This study concludes that it contributes to drawing up a clear plan for monetary policy that ensures the stability of the economic situation and helps in confronting the challenges that Islamic countries face in their monetary policy.